1986
DOI: 10.1152/ajpheart.1986.251.6.h1217
|View full text |Cite
|
Sign up to set email alerts
|

Studies of functional site of origin of native coronary collaterals

Abstract: Studies were performed to determine the pressure at the origin of the native coronary collaterals (Pstem) and thus assess the contribution of collaterals arising from proximal conduit coronary vessels vs. those arising from distal microvessels. Nine isolated blood-perfused dog hearts were studied. Aortic pressure was maintained at 80 mmHg. Collateral flow to the circumflex perfusion field was measured (radioactive microspheres) repeatedly before and after successive 25-micron nonradioactive microsphere emboliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…There are several reasons why this likely did not influence our results. The majority of native collaterals interconnect large coronary arteries and thus arise and insert proximal to major sites of resistance in the coronary circulation.24 25 Thus, the driving pressure for any flow reaching the circumflex via collaterals is similar to circumflex pressure measured by the catheter distal to the hydraulic occluder. Under this circumstance, analysis of pressure/flow relationships calculated with pressure measured through this catheter would be valid whether or not collateral perfusion contributed to total myocardial perfusion of the circumflex.…”
Section: Methodsmentioning
confidence: 99%
“…There are several reasons why this likely did not influence our results. The majority of native collaterals interconnect large coronary arteries and thus arise and insert proximal to major sites of resistance in the coronary circulation.24 25 Thus, the driving pressure for any flow reaching the circumflex via collaterals is similar to circumflex pressure measured by the catheter distal to the hydraulic occluder. Under this circumstance, analysis of pressure/flow relationships calculated with pressure measured through this catheter would be valid whether or not collateral perfusion contributed to total myocardial perfusion of the circumflex.…”
Section: Methodsmentioning
confidence: 99%
“…eosinophil peroxidase (EPO) and myeloperoxidase (MPO), respectively (103,135,184,341) (178). Interestingly, the rate of inactivation of catalase via H 2 O 2 production is the highest in Type II cells (178).…”
Section: Fig 2 Sources Of Exogenous Inhalational and Endoge-mentioning
confidence: 99%
“…Furthermore, the manipulations in these experimental studies themselves posed several limitations to the interpretation of the data (5), and the extension to human pathophysiology. Still, the experimental data suggested that a pressure drop before the collateral takeoff was the main determinant of steal in the presence of a maximally dilated ischemic microcirculation distal to the occlusion without a vasodilatory reserve (4,5,30). Our data clearly show that in man this is not uniformly observed in patients with CTOs, and that a preserved vasodilatory reserve of the microcirculation may prevent coronary steal.…”
Section: Discussionmentioning
confidence: 56%